Beloken blikvelden in de Lage Landen: Eenentwintigste-eeuwse receptie van Nederlandse vertalingen van Afrikaanse poëzie - T’Sjoen, Yves (Tydskrif vir Letterkunde, 2013)
The South African poets Ingrid Jonker, Antjie Krog and Ronelda S. Kamfer are part of the literary system of the Low Countries. Their introduction in the Netherlands and Flanders was accomplished by translations into Dutch. An analysis of the role and the image-building of foreign literature in the Dutch-speaking world is important for (the study of) literary historiography. The presence and the reception of the three selected South African poets and their works are documented in this paper. Critics are not only interested in the literary production of national authors but also in the poetry of foreign writers (mainly available through translations). In this way, poets and their works start functioning in the literary poly-system of the Netherlands and Flanders. The manner in which images are created tells us something about the presence of Jonker, Krog and Kamfer in contemporary Dutch literature. Not only are the reactions of readers (or critics) fundamental to the study of literary reception, the way in which these writers and their poetry have gained particular positions in the literary system should also be part of the research. Revealing questions deal with the role played by intermediaries, the selection criteria for poems in anthologies, translation strategies, the promotion by commercial publishers. Foreign literature is interwoven with the poetical discourses of a national literary system. In this respect, the translated poetry by the three selected South African (Afrikaans writing) female authors is part of the borderless (Dutch) literature.